KUALITAS MENGAJAR GURU DALAM TERANG SERVANT LEADERSHIP - Yohanes Tony Santoso (Jurnal Visionida, 2022)
Many flow of thoughts about topic of leadership emerged over years. Among these are transformative leadership, transactional leadership, democratic leadership, servant leadership and so on. The concept of servant leadership stands out among these other approaches to leadership because of its widespread use in the classroom. This paper explored the features of servant leadership and their implications for the field of education, with the goal of gaining a better understanding of how these ideas might be used in the classroom. In this research, we examine three different perspectives on leadership: the leader's own, the followers', and the combined. Literature study methods, including the Systematic Literature Review (SLR) and the deduction to induction analysis methods, were used for this investigation. Servant leadership is characterized by its ability to listen to others, to sympathize with them, to heal, to be aware, to persuade, to create concepts, to have visionaries, to exercise stewardship, to be committed to the development of its members, and to construct communities. The ability to prioritize service activities, inspire students, and meet their needs; the ability to explore students' potential; the ability to set high performance standards to provide intellectual stimulation to students; the ability to solve problems in order to develop strength; the ability to place themselves; these are all hallmarks of leadership in the field of leadership education. Leadership in education can be implemented in a variety of settings, including classroom instruction, student extracurriculars, internships, and formal relationships between superiors and subordinates who share a commitment to service.